Mekanisme Pengelolaan Administrasi Keuangan pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidoarjo Ditinjau dari Peraturan Gubernur Jawa Timur No 11 Tahun 2024 (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
The development of information technology has driven digital transformation in government administration, including in East Java Province, which has confirmed the implementation of the Electronic-Based Government System (SPBE) through Governor Regulation No. 11 of 2024. This study aims to examine the financial management mechanisms in the Population and Civil Registration Office of Sidoarjo Regency based on this regulation. The method used is descriptive qualitative with an approach of interviews, observation, and document analysis. The results of the study show that the implementation of SPBE at the Sidoarjo Dispendukcapil covers four main stages: planning and budgeting, implementation and administration, recording and reporting, as well as control and supervision. Digitization through the SIPD and SIKSDA systems has succeeded in improving the efficiency, accuracy, and transparency of financial management, despite technical obstacles such as limited connectivity and server stability. Human resource development through regular training is key to the successful adaptation of this technology. This study recommends improving technological infrastructure, integrating application systems, and continuously developing human resource competencies to support transparent, effective, and accountable governance in local government. These findings make an important contribution to strengthening digital financial administration management in the era of modern governance.